Лінгвістичні особливості маніпулятивних дій у комунікації - Альбота, Соломія (Видавництво Львівської політехніки, 2018)
The article focuses on the psycholinguistic mechanism of the manipulative models. In terms of transactional analysis of the dialogues representing manipulation acts the linguistic as well as psychological mutual effects are revealed. Such linguistic constructions as presuppositions expressed both in explicit and implicit ways are discovered.
Keywords: communication; manipulative model; transactional analysis; pressuposition